Gambaran Faktor Resiko Kejadian BBLR di RSUD.dr. Rasidin Padang Tahun 2023 - Firda Damba Wahyuni; Ira Sri Budiarti (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
Babies with low birth weight (LBW) is still a problem throughout the world because it is a cause of illness and death in the newborn period. The prevalence of LBW estimated 15% of all births in the world with a limit of 3.3% -38% and is more common in developing countries or low socio-economic. Objective knows Overview Risk Factors Genesis low birth weight (LBW) in RSUD.dr.Rasidin Padang in the Year 2016 in dr. Rasidin Padang in 2023 there were 47 mothers who give birth to babies with low birth weight. This type of research is descriptive to see an overview of a study. This study was conducted in mei 2023 until juni 2023 in hospitals Dr.Rasidin Padang, the samples in the study were 47 respondents, data collection techniques are data from hospital medical records, sample collection technique Total Sampling technique. Data processing techniques with editing, coding, data entry, tabulating, cleaning and data analysis with univariate analysis. From the results, the risk of maternal age (59.6%), risk parity (55.3%), the risk of birth spacing (61.7%) of risk factors that affect the incidence of low birth weight. There is a description of risk factors at birth mothers with LBW.